The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1744-7348.2007.00196.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential of partial rootzone drying as an alternative irrigation technique for potatoes (Solanum tuberosum)

Abstract: The increasing demands on limited water supplies worldwide require the adoption of more efficient irrigation techniques for sustainable production in agriculture. Partial rootzone drying (PRD) is one of the techniques that offer potential saving of irrigation water. This technique involves alternate irrigation to two sides of a plant root system. The studies reported here investigated PRD irrigation regimes and the optimum time of starting PRD in potatoes grown in a protected environment. In the first experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 35 publications
2
31
0
1
Order By: Relevance
“…Kondisi cuaca akan menentukan laju penguapan air (evapotranspirasi). Tingkat pembasahan dan pengeringan setiap bagian akar antara lain bergantung fase pertumbuhan, laju evaporasi, dan keseimbangan air tanah (Saeed et al 2008). Lebih lanjut Marsal et al (2008) menjelaskan bahwa perbedaan antara PRD (partial root zone drying) atau PSDA dan pengairan lainnya secara umum menunjukkan perbedaan laju evaporasi.…”
Section: Hasil Dan Pembahasan Penelitian Tahap Pertamaunclassified
“…Kondisi cuaca akan menentukan laju penguapan air (evapotranspirasi). Tingkat pembasahan dan pengeringan setiap bagian akar antara lain bergantung fase pertumbuhan, laju evaporasi, dan keseimbangan air tanah (Saeed et al 2008). Lebih lanjut Marsal et al (2008) menjelaskan bahwa perbedaan antara PRD (partial root zone drying) atau PSDA dan pengairan lainnya secara umum menunjukkan perbedaan laju evaporasi.…”
Section: Hasil Dan Pembahasan Penelitian Tahap Pertamaunclassified
“…Our results consent with those of Ben Nouna et al (2016) who showed that PRD60 treatment improved the WUE of potato by (10.9 and 10.2%) and (25.8 and 19.7%) compared to full irrigation and PRD80. Also, Saeed et al (2008) found that PRD irrigation used 29% less water and improved the WUE by 19%. Similarly, Xie et al (2012) reported that the PRD50 treatment used 50% less water and increased the WUE by 48%.…”
Section: IVmentioning
confidence: 99%
“…Sadras (2009), confirmed that the use of PRD irrigation and deficit irrigation have allowed a productivity increase of 82% and 76% respectively compared to conventional irrigation with a non-significant reduction in yield. Yang et al, (2011) studied for three years (2006)(2007)(2008), the water use efficiency of durum wheat under three different irrigation regimes of PRD (30,40 and 50% of the ETM). The results showed a significant improvement in water productivity from 12 to 71.4%.…”
Section: Introductionmentioning
confidence: 99%
“…Water and nitrogen are two key resources considered main factors in limiting plant growth with approximately 70% of available water being used for irrigation (Medici et al, 2007;Parry, 2008, 2009;Saeed et al, 2008;Andrews et al, 2009;da Silva et al, 2009). Yet, the control of irrigation is barely precise (Souza and Folegatti, 2010).…”
Section: Introductionmentioning
confidence: 99%